Apoptosis-independent organoruthenium anticancer complexes that overcome multidrug resistance: self-assembly and phenotypic screening strategies. Issue 5 (14th March 2017) - Chow, Mun Juinn; Alfiean, Mohammad; Pastorin, Giorgia; Gaiddon, Christian; Ang, Wee Han
Abstract : Phenotypic screening on a library of combinatorial self-assembled organoruthenium complexes revealed constructs that act on refractory cancers via apoptosis-independent pathways. Abstract : Multidrug resistance is a major impediment to chemotherapy and limits the efficacies of conventional anticancer drugs. A strategy to bypass multidrug resistance is to develop new drug candidates capable of inducing apoptosis-independent programmed cell death. However, cellular pathways implicated in alternative programmed cell death are not well-elucidated and multifactorial, making a target-based discovery approach a challenge. Here, we show that a coordination-directed three-component assembly and phenotypic screening strategy could be employed as a viable alternative for the identification of apoptosis-independent organoruthenium anticancer agents. Through an on-plate synthesis and screening of 195 organoruthenium complexes against apoptosis-sensitive and -resistant cancers, we identified two apoptosis-independent hits. Subsequent validation of the two hits showed a lack of induction of apoptotic biomarkers, a caspase-independent activity and an equal efficacy in both apoptosis-sensitive and -resistant colorectal cancers. This validated their apoptosis-independent modes-of-action, paving the way as potential candidates for the treatment of highly-refractory cancer phenotypes.